Membranes with functionalized nanomaterials : current and emerging research trends in membrane technology - Dutta, Suman; Hussain, Chaudhery Mustansar (Elsevier, 2022)
Membranes with Functionalized Nanomaterials: Current and Emerging Research Trends in Membrane Technology provides researchers and practitioners with basic and advanced knowledge of sustainable membrane technology. The book summarizes recent progress made in novel functionalized nanomaterials (FNMs) used in modern membrane technology. It gives a comprehensive overview of state-of-the-art technologies in the field of nanomaterial-based membranes and provides in an in-depth and step-by-step way the foundational scientific knowledge on various sustainable membranes with FNMs technologies and their impact on society and in various industries. In addition, readers get a handbook in a compact form with various aspects of FNMs-based sustainable membranes.